Dead Region Time Evolution and Afterpulses Development in SQS - Lima, E. P. de (1984)
The dead length, 6, for t > 20 ms is well approximated by d=d0 exp(-t/t) for mixtures of argon-isobutane with benzene or TEA. d0 varies in an approximate linear way with the streamer charge and the systematics of t regarding the high voltage is also presented. Afterpulses are associated not only with wall effects but also with photoionization in the gas mixture itself. Interpretation of the data is attempted